Splat the Cat with a bang and a clang - Hsu Lin, Amy.; Scotton, Rob.; Farley, Rick.; Eberz, Robert (New York : Harper, 2013)
Splat's friends are having a rehearsal for their cool new band, the Cat Gang. But something's missing...it just doesn't feel right without Splat! Everyone wants Splat to join the band. But Splat can't sing and he doesn't play an instrument! What can he do that is perfect for the Cat Gang?
Keywords: Cats -- Juvenile fiction; Bands (Music) -- Juvenile fiction; Cats -- Fiction; Rock groups -- Fiction